Spatial patterns and behaviour at Dunefield Midden - Reeler, Claire (Department of Archaeology, 2016)
An analysis of the spatial patterning present in the arrangement of material and features at the site of Dunefield Midden, is presented in this thesis. All items from the site are analysed, except the remains of large fauna. The site of Dunefield Midden is situated about two kilometres north of Eland's Bay on the Cape West coast, South Africa. Radiocarbon dates indicate that the site was occupied about 670 years B.P. The nature of the food remains and artefacts from this site suggests a single occupation, for a limited period, by a group of hunter-gatherers. Features from the site examined in detail include ash features (such as hearths, roasting pits and ash dumps) and dumps (in particular, a feature called the 'main dump'). Comparisons with ethnographic and ethnoarchaeological material are made to aid the process of interpretation. Other features common to ethnographic hunter-gatherer campsites, but for which there is no evidence at Dunefield Midden (such as structures), are discussed. The type of site, possible length of occupation and number of people are discussed from the analysis of features and other material. Suggestions are made that the site was a base camp occupied by between ten and twenty-five people for a month to a month and a half. Finally, conclusions are made about the nature of the behaviours which caused the spatial patterning evident on the site. The level of detail reached in the interpretations of patterning and behaviour is far greater than that possible from more complex, deeply stratified sites. Thus, the value of researching different kinds of sites is shown. The use of a Geographic Information System to analyse information and create distribution maps is unique in spatial archaeological studies. The use of this system shows its value as a new technology of great potential use to all archaeologists. The spatial autocorrelation test of randomness of distributions is also introduced and is compared to other statistical tests used by archaeologists previously. This test is applied to distributions of items from the site, produced with the aid of the Geographic Information System. The use of site indices describes a method of normalising distributions, with the possibility of using satellite technology to analyse these distributions. This thesis, therefore, reaches a deeper level of interpretation of human behaviour at one particular site, than generally has been achieved previously. It also introduces new techniques and technologies particularly suited to this analysis and potentially of use to other archaeologists, even in different fields of study.